2004
DOI: 10.1074/mcp.m300133-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Qualitative and Quantitative Proteomic Analysis of Clinical Hepatocellular Carcinoma Using Laser Capture Microdissection Coupled with Isotope-coded Affinity Tag and Two-dimensional Liquid Chromatography Mass Spectrometry

Abstract: Laser capture microdissection (LCM) is a powerful tool that enables the isolation of specific cell types from tissue sections, overcoming the problem of tissue heterogeneity and contamination. This study combined the LCM with isotope-coded affinity tag (ICAT) technology and two-dimensional liquid chromatography to investigate the qualitative and quantitative proteomes of hepatocellular carcinoma (HCC). The effects of three different histochemical stains on tissue sections have been compared, and toluidine blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(113 citation statements)
references
References 39 publications
6
107
0
Order By: Relevance
“…K protein is upregulated in malignant cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004), and it regulates the expression of genes involved in mitogenic responses, indicating that it has a direct role in cancerogenesis (Michelotti et al, 1995(Michelotti et al, , 1996Ostrowski et al, 2004). We have shown that following mitogenic stimulation, K protein is recruited to gene loci known to be upregulated in malignant states, including c-myc .…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…K protein is upregulated in malignant cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004), and it regulates the expression of genes involved in mitogenic responses, indicating that it has a direct role in cancerogenesis (Michelotti et al, 1995(Michelotti et al, , 1996Ostrowski et al, 2004). We have shown that following mitogenic stimulation, K protein is recruited to gene loci known to be upregulated in malignant states, including c-myc .…”
mentioning
confidence: 86%
“…As K protein is upregulated in tumour cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004) and modulates the expression of genes involved in mitogenic responses (Michelotti et al, 1995(Michelotti et al, , 1996Mandal et al, 2001;Ostrowski et al, 2004), altering its properties and introduction of a new phosphorylation site could make K protein either more or less conducive for the cellular processes that lead to tumorigenic state. If so, identification of this novel tumour-associated K protein isoform may prove to be a useful diagnostic, prognostic and/or therapeutic indicator.…”
Section: P<005mentioning
confidence: 99%
“…In particular, MS is a powerful tool for resolving the complexity of cancer signaling pathways. With regard to HCC, qualitative proteomics has been performed on resected tumor material (12), laser-capture microdissected material from tissue sections (13,14), and primary hepatocytes or serum derived from patients (15,16). These studies (17,18) identified HCC biomarkers such as glutamine synthetase and heat shock protein 70 (Hsp70) that are currently in use for diagnosis (19,20).…”
mentioning
confidence: 99%
“…Different isotope labeling methods have been used in order to compare proteins expression. ICAT was first used to investigate proteomes of hepatocellular carcinoma (Li et al, 2004; isotopic labeling was then used for proteomic analysis of ductal carcinoma of the breast (Zang et al, 2004). Microdissected tissue pieces can also be investigated after their status linked to markers of interest.…”
Section: Laser Capture Microdissection (Lcm)mentioning
confidence: 99%